2016
DOI: 10.1038/srep24935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fat distribution and Bone quality with Trabecular Bone Score (TBS) in Healthy Chinese Men

Abstract: Whether fat is beneficial or detrimental to bones is still controversial, which may be due to inequivalence of the fat mass. Our objective is to define the effect of body fat and its distribution on bone quality in healthy Chinese men. A total of 228 men, aged from 38 to 89 years, were recruited. BMD, trabecular bone score (TBS), and body fat distribution were measured by dual-energy X-ray absorptiometry. Subcutaneous and visceral fat were assessed by MRI. In the Pearson correlation analysis, lumbar spine BMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
3
22
1
1
Order By: Relevance
“…In contrast, other studies have reported that visceral fat may have a negative association with bone mineral status and correlates inversely with BMD and bone structure. 10,34,35 However, in our study, we did not find this association with bone microarchitecture. Consistent with our findings, Bredella et al 10 also concluded that both BMA and VAT may have a detrimental effect on BMD.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In contrast, other studies have reported that visceral fat may have a negative association with bone mineral status and correlates inversely with BMD and bone structure. 10,34,35 However, in our study, we did not find this association with bone microarchitecture. Consistent with our findings, Bredella et al 10 also concluded that both BMA and VAT may have a detrimental effect on BMD.…”
Section: Discussioncontrasting
confidence: 96%
“…Our data are consistent with other reports that did not show any association between adiposity, as assessed by DXA, and BMD. In contrast, other studies have reported that visceral fat may have a negative association with bone mineral status and correlates inversely with BMD and bone structure . However, in our study, we did not find this association with bone microarchitecture.…”
Section: Discussionsupporting
confidence: 93%
“…[35][36][37] In contrast, previous studies found that adipose tissue was positively correlated with BMC, 38 but excessive adipose tissue could lead to decreased BMC, 39 and adipose tissue at different parts might exert different effects on bone. 33 Our results showed positive effects on BMC and LS BMD, which might be due to that a certain range of increase in AVF might have a positive impact on BMD, while an excessive increased AVF might lead to a negative effect. 33 In addition, the adipose tissue, especially the visceral fat not only affects the homeostasis of the body's energy but also affects other processes including bone metabolism by releasing a variety of adipokines.…”
Section: Discussionmentioning
confidence: 47%
“…There were studies found that AVF had a negative impact on BMD, it is regarded as a risk factor for bone loss and increased obese fractures. [12][13][14][15] Studies showed that adipose tissue showed a positive effect on bones only through mechanical loading, 33 while the others are more complex nonweight-bearing effects. 34 Furthermore, epidemiological studies have found adipose tissue showing a positive correlation with BMD and BMC.…”
Section: Discussionmentioning
confidence: 99%
“…BMD, as measured by dual X-ray absorptiometry (DXA), has been the gold standard tool both for osteoporosis detection and monitoring of treatment efficacy. Unfortunately, BMD alone cannot explain the inconsistency between fat and bone metabolism [8]. The mechanism in which obesity may increase the risk of fractures is unknown but probable V. Povoroznyuk, A. Musiienko, and N. Dzerovych are with D. F. Chebotarev Institute of gerontology NAMS Ukraine, Kyiv, Ukraine (e-mail: okfpodac@ukr.net, musienko_anya@ukr.net, zeronat@ukr.net).…”
Section: Introductionmentioning
confidence: 99%